(untitled) (Zoological Archives: An International Journal, 2026)
Rapidly diversifying lineages – adaptive radiations that generate disproportionate species richness over short evolutionary timescales – represent natural experiments in accelerated evolution, yet the molecular and morphological rate correlates of radiation tempo remain incompletely characterised across animal phyla. This study estimated lineage-specific molecular evolutionary rates (substitution rates for 12 genes spanning synonymous, non-synonymous, and non-coding categories), morphological diversification rates (rate of disparity accumulation from geometric morphometrics), and net diversification rates (speciation minus extinction; BAMM v2.5) for 28 animal adaptive radiation lineages across eight phyla (Vertebrata, Arthropoda, Mollusca, Echinodermata, and four invertebrate phyla) using time-calibrated phylogenies (24 published, 4 newly generated) encompassing 2,840 species. Molecular substitution rates were significantly positively correlated with net diversification rates across lineages (r = +0.68, p < 0.001), with non-synonymous rates (dN) showing the strongest correlation (r = +0.74) and synonymous rates (dS) the weakest (r = +0.28), consistent with positive selection at protein-coding loci contributing to accelerated diversification. Morphological disparity accumulation rate was uncorrelated with molecular rate (r = +0.14, p = 0.48), indicating that molecular evolutionary acceleration does not necessarily translate into rapid morphological diversification. BAMM identified 18 rate shifts across the combined phylogeny, all associated with key ecological opportunity events: island colonisation (n = 8), prey base expansion (n = 6), and habitat transition (n = 4). Lineage-specific non-synonymous substitution rate was the strongest single predictor of radiation net diversification rate (partial r = +0.68 after controlling for body size, generation time, and ecological opportunity index). These results support the molecular evolutionary rate hypothesis for adaptive radiation: elevated dN rates associated with positive selection on ecologically relevant traits facilitate rapid phenotypic diversification and competitive exclusion enabling diversification into available niche space